Unsteady analysis of the cold energy storage heat exchanger in a liquid air energy storage system. (1st March 2022) - Chen, Jiaxiang; Yang, Luwei; An, Baolin; Hu, Jianying; Wang, Junjie
Abstract: Liquid air energy storage (LAES) is promising in the large scale energy storage field. The heat exchanger (Hex) in a LAES system using liquid phase working mediums for cold energy storage (CES) works discontinuously for the intermittent characteristic of the LAES. Variable temperature distribution exists in the Hex for CES (Hex-CES) in the intermittent process, and degrades the performance of the CES unit. In this paper, a computational model is constructed for the unsteady process in the Hex-CES of a 100 kW LAES system using liquid phase working mediums for CES to study the unsteady effect. The established steady temperature gradient is decreased gradually in the static process during which the LAES stops working and basically turns to zero gradient 12 h later. In the next operation cycle, it takes 34.8 min to reestablish the steady temperature gradient in the Hex-CES. Two methods to reduce the unsteady effect are proposed, the influence of key parameters on weakening the unsteady effect is investigated, and the optimal operation parameters in the static process are obtained. The results obtained in this paper are expected to provide the basis for the application of CES using liquid phase mediums and enhance the performance of LAES. Highlights: Unsteady effect of liquid air energy storage system was first analyzed. A computational model for the unsteady heat transfer was developed and verified. Two methods were proposed to reduce the unsteady effect. The influence of the proposed methods on the unsteady effect was originally studied.